Strength characteristics of a heat-resistant metal-matrix composite inconel 625–5%NiTi–TiB2 alloy fabricated by direct laser deposition under shock-wave loading - Razorenov, Sergey V.; Garkushin, Gennady V.; Savinykh, Andrey S.; Promakhov, Vladimir V.; Matveev, Alexey E.; Klimova-Korsmik, Olga G.; Vorozhtsov, Alexander B. (Metals)
The Hugoniot elastic limit and spall strength were measured for a heat-resistant metalmatrix composite Inconel 625–5%NiTi–TiB2 alloy additive manufactured (AM) by direct laser deposition. The strength characteristics of the alloy were obtained from the analysis of the complete wave profiles recorded with a VISAR laser Doppler velocimeter during shock-wave loading of the samples. The samples were loaded using a PP50 pneumatic gun or ad hoc explosive devices along and across the material deposition direction in order to determine the strength anisotropy of the AM alloy under study. The maximum shock compression pressure was ~7 GPa, and the strain rate under tension before spalling varied in the range of 105–106 s–1. Kinetic dependencies of elastic/plastic transition and critical fracture stresses vs. loading conditions were plotted. It was shown that the Hugoniot elastic limit of the alloy under study decreases as the shock wave travels into the sample, while the spall strength increases as the material’s strain rate increases at the moment of spall fracture. A comparison of the strength characteristics of the Inconel 625–NiTi–TiB2 composite alloy with the original Inconel 625 alloy has shown that an addition of 5% of powder based on NiTi-TiB2 leads to a decrease in its elastic limit and critical fracture stresses upon spalling by more than 10%. The alloy under study demonstrates anisotropy of strength properties relative to the material deposition direction